Effect of cerebral small vessel disease on cognitive function and TLR4 expression in hippocampus. (September 2019) - Zhang, Yamin; Zhang, Yi; Wu, Ruipeng; Gao, Fulin; Zang, Peixi; Hu, Xiaojuan; Gu, Cheng
Highlights: We provide reference for the diagnosis and treatment of CSVD in clinical practice. CSVD rats have poor cognitive function and neurological functions. We infer that TLR4 may affect the cognitive function of CSVD rats. TLR4 is expected to be a target in treatment of CSVD. Abstract: The aim of this study was to explore the differences in cognitive and neurological functions between cerebral small vessel disease (CSVD) rats and normal rats, as well as to study the Toll- like receptor 4 (TLR4) expression in the hippocampus of CSVD rats to understand its role in this brain structure. Forty male, 12-week old, specific pathogen-free (SPF), spontaneously hypertensive rats (SHRs) were used as the observation group, while 20 12-week old, SPF, Wistar male rats were used as the control group. After each measurement, 10 rats in the observation group and 5 in the control group were decapitated to collect samples for determining the expression of TLR4 in the hippocampus. At T1, difference in the latency of rats in the observation group showed no statistically significance ( p = 0.836), while at T2, T3 and T4, the observation group showed longer latency than did the control group ( p < 0.001). In addition, the latency of SHRs at T1 was the shortest ( p < 0.05) compared to the follow-ups (T2-T4) and were followed sequentially by T2, T3, and T4 ( p < 0.05). The latency was shorter than those at T1 and T2, and the shortest latency was found at T4 ( p < 0.05). CSVD rats exhibited poor cognitive and neurological functions compared to normal rats and high expression of TLR4 in the hippocampus. Based on these results, we suggest that TLR4 affects the cognitive function of CSVD rats, and, thus, may be a valuable target in the treatment of CSVD.